2021
DOI: 10.3390/cancers13246157
|View full text |Cite
|
Sign up to set email alerts
|

Current Limitations and Perspectives of Chimeric Antigen Receptor-T-Cells in Acute Myeloid Leukemia

Abstract: Adoptive transfer of gene-engineered chimeric antigen receptor (CAR)-T-cells has emerged as a powerful immunotherapy for combating hematologic cancers. Several target antigens that are prevalently expressed on AML cells have undergone evaluation in preclinical CAR-T-cell testing. Attributes of an ‘ideal’ target antigen for CAR-T-cell therapy in AML include high-level expression on leukemic blasts and leukemic stem cells (LSCs), and absence on healthy tissues, normal hematopoietic stem and progenitor cells (HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 178 publications
0
7
1
Order By: Relevance
“…Therefore, we acknowledge that aITGB2 CAR-T is unlikely to be a curative therapy for all AML patients. However, for tumors with elevated expression of this target, in our in vitro and in vivo experiments we did not observe distinctly decreased efficacy versus anti-CD33 CAR-T, a leading AML CAR-T target but with marked toxicity concerns 19 . The favorable safety profile of aITGB2 CAR-Ts also may create future opportunities for multi-targeting CARs versus two or more antigens with complementary but heterogeneous tumor expression patterns, particularly if the additional antigens beyond active integrin-2 also are non-myeloablative.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Therefore, we acknowledge that aITGB2 CAR-T is unlikely to be a curative therapy for all AML patients. However, for tumors with elevated expression of this target, in our in vitro and in vivo experiments we did not observe distinctly decreased efficacy versus anti-CD33 CAR-T, a leading AML CAR-T target but with marked toxicity concerns 19 . The favorable safety profile of aITGB2 CAR-Ts also may create future opportunities for multi-targeting CARs versus two or more antigens with complementary but heterogeneous tumor expression patterns, particularly if the additional antigens beyond active integrin-2 also are non-myeloablative.…”
Section: Discussioncontrasting
confidence: 56%
“…As an initial proof of principle, we apply structural surfaceomics to target discovery in acute myeloid leukemia (AML), a frequently-diagnosed hematologic malignancy with dismal prognosis 17 . In contrast to B-cell acute lymphoblastic leukemia, chimeric antigen receptor (CAR) T cells in AML have generally led to either significant toxicities or disappointing clinical efficacy 18, 19 . As demonstrated in an integrated study of the AML transcriptome and surface proteome 16 , one major hurdle to CAR-T therapy for AML is lack of optimal immunotherapy targets.…”
Section: Introductionmentioning
confidence: 99%
“…Special subtypes of lymphoma have selected corresponding specific antigens as targets, such as CD30 for anaplastic large cell lymphoma (ALCL) and Hodgkin lymphoma (HL) [52][53][54]. Acute myeloid leukemia (AML) is a highly heterogeneous tumor, and there are a lot of studies on its targets, including CD33, CD123, CLL1 (CD371), CD25, CD117, Tim3, NKG2D, CD44, CD96, and CD38, or the combination of the above targets [5,12,17,18,[55][56][57][58][59][60]. Although studies on solid tumors have made some achievements, searching for solid tumor-specific or associated antigens is still an interesting field for researchers.…”
Section: Overview Of the Car-t Targets In Various Tumorsmentioning
confidence: 99%
“…Perna et al used large surface genome datasets from malignant (AML) and normal tissues and found CD123, CLEC12A, and CD33 to be highly expressed on AML blasts at >75% expression but also with high expression on normal hematopoietic stem cells with the possibility of introducing many side effects in patients [ 37 ]. Despite this risk, several CAR T-cells for AML are in development targeting CD33, CD123, and CLEC12A, and patients are currently being recruited for clinical trials [ 38 ]. FLT3 is also expressed on other hematologic malignancies, particularly B-lineage acute lymphocytic leukemia (ALL), and it has also been reported to be amplified on some solid tumors like breast cancer, colorectal cancer, and gastric cancer [ 39 ].…”
Section: The Choice Of Flt3 As Target For Car T-cell Therapymentioning
confidence: 99%